2008
DOI: 10.1002/joc.1806
|View full text |Cite
|
Sign up to set email alerts
|

Summer rain fall duration and its diurnal cycle over the US Great Plains

Abstract: By diagnosing the hourly station rain gauge data set for the 1981-1999 periods, it is found that the rainfall diurnal cycle is closely related to its duration during summer (June-August) over the Great Plains [(GP), 100-90°W, 35-45°N]. Short-duration rainfall events (an event of 1 h in duration) occur more frequently in summer, and they tend to have two diurnal maxima over the GP, with one in the early morning [0400-0600 local solar time, (LST)] and the other in the afternoon (1500-1700 LST). Long-duration rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…It shows the climatic characteristics of the study region and is often regarded as the basis for the regional forecasting of MCSs including its precipitation. The FT of MCSs tracked in our study showed two peaks, similar to many midlatitude areas (Hamilton 1981;Dai 2001;Tian et al 2005;Chen et al 2009). The major peak was in the late afternoon and early evening around 1800 LST when strengthening CAPE occurs after 1400 LST (Dai 2001 …”
Section: B Distribution Of Cloud and Precipitation Parametersmentioning
confidence: 80%
“…It shows the climatic characteristics of the study region and is often regarded as the basis for the regional forecasting of MCSs including its precipitation. The FT of MCSs tracked in our study showed two peaks, similar to many midlatitude areas (Hamilton 1981;Dai 2001;Tian et al 2005;Chen et al 2009). The major peak was in the late afternoon and early evening around 1800 LST when strengthening CAPE occurs after 1400 LST (Dai 2001 …”
Section: B Distribution Of Cloud and Precipitation Parametersmentioning
confidence: 80%
“…The precipitation intensity was defined as the accumulated rainfall amount during each hour in which precipitation occurred (units: mm h −1 ). Following Yu et al (2007a) and Chen et al (2009), the duration of a rainfall event was defined as the number of hours from the beginning to the end of a rainfall event, and the corresponding intermittence should be no longer than 1 h. Thus, those rainfall events with intermittences greater than 1 h were regarded as two different rainfall events. Generally, precipitation decreases from more than 1800 mm year −1 in southeastern coastal areas to less than 50 mm year −1 in northwestern inlands (Qian and Lin, 3151 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The diurnal cycle of precipitation is another unique feature of the Great Plains climate, with the rainfall reaching a maximum diurnal peak overnight during the summer months [e.g., Wallace , ; Carbone et al ., ; Carbone and Tuttle , ; Surcel et al ., ; Berenguer et al ., ]. Its nocturnal precipitation peak comes from three primary sources: eastward propagation of storms initiated over the Rocky Mountains in the late afternoon [ Carbone et al ., ; Jiang et al ., ; Carbone and Tuttle , ; Chen et al ., ], a mountain‐plain solenoid circulation that suppresses day‐time convection and promotes nocturnal convection east of the Rocky Mountains [ Dai et al ., ; Carbone and Tuttle , ], and transportation of energetic air into the Plains by the nocturnal LLJ [ Higgins et al ., ; Carbone and Tuttle , ; Pu and Dickinson , ]. Simulation of this diurnal cycle is expected to be significantly improved through increasing horizontal resolution [ Lee et al ., ; Clark et al ., , ; Hohenegger et al ., ], especially with the use of CP modeling to explicitly represent convection [ Clark et al ., , ].…”
Section: Introductionmentioning
confidence: 99%